Waqf Fundraising Strategies: A Comparison between Indonesia and Malaysia - Abdullah, Yahya; Rusydiana, Aam Slamet (SMART Insight, 2023)
The article aims to understand and analyze the various strategies that have been implemented in raising waqf funds in Indonesia and Malaysia. The data sources used come from Scopus indexed journals, ensuring the accuracy and credibility of the information. The results of the research show that there are ten main strategies that have been implemented in the context of waqf in Indonesia and Malaysia, namely digitalization and information technology strategies, government policy strategies, local cultural system strategies, management strategies, marketing and waqf objects, new strategies offered, strategies to strengthen legal legality, strategies for understanding the behavior of waqf donors, waqf education and socialization strategies, waqf institutional strategies and word of mouth strategies. Thus, this article provides a comprehensive view of waqf fund collection strategies in Indonesia and Malaysia, which can be a basis for further development in the context of Islamic finance and waqf fund management.